2016
DOI: 10.1038/srep18729
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Fluoride Bioavailability in the Biofilms of Different Oral Surfaces after Amine Fluoride and Sodium Fluoride Application

Abstract: It was the aim of this study to investigate differences in fluoride bioavailability in different oral areas after the application of amine fluoride (AmF) and sodium fluoride (NaF). The null hypothesis suggested no differences in the fluoride bioavailability. The tongue coating was removed and biofilm samples from the palate, oral floor and cheeks were collected. All subjects brushed their teeth with toothpaste containing AmF or NaF. Specimens were collected before, as well as immediately after and at 30 and 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…As confirmed in this study, 500 ppm of sodium fluoride alone (B) could only slightly modify the erosion-preventive effect of the physiological pellicle. In comparison, the amphiphilic properties of amine fluoride such as contained in elmex Kariesschutz might have increased its affinity to pellicle proteins resulting in a slower clearance and a modification of the pellicle composition or –density, respectively 37 , 40 . Certainly, only the NaF/AmF/SnCl 2 -containing mouthrinse (D) could reduce the acid-induced calcium- and phosphate release of the physiological in situ pellicle significantly even under severe erosive conditions.…”
Section: Discussionmentioning
confidence: 99%
“…As confirmed in this study, 500 ppm of sodium fluoride alone (B) could only slightly modify the erosion-preventive effect of the physiological pellicle. In comparison, the amphiphilic properties of amine fluoride such as contained in elmex Kariesschutz might have increased its affinity to pellicle proteins resulting in a slower clearance and a modification of the pellicle composition or –density, respectively 37 , 40 . Certainly, only the NaF/AmF/SnCl 2 -containing mouthrinse (D) could reduce the acid-induced calcium- and phosphate release of the physiological in situ pellicle significantly even under severe erosive conditions.…”
Section: Discussionmentioning
confidence: 99%
“…decreasing the development of the plaque [37] and has antibacterial activity against streptococci mutans [38]. which are accumulated in the oral biofilm [12].…”
Section: Discussionmentioning
confidence: 99%
“…It has been discussed whether salivary sediment acts as fluoride reservoir releasing fluoride slowly for a prolonged time. Fluoride bioavailability varies also in the different oral niches where different surfaces influence the fluoride bioavailability [12, 47, 48]. Other studies investigated the fluoride bioavailability in dental plaque and reported elevated fluoride concentrations after toothbrushing [44, 46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, frequent applications of rather low concentrations of fluorides are recommended to inhibit demineralization and enhance remineralization 5 . The tongue may serve as an important fluoride reservoir, as well 6 . For remineralisation in vivo , the oral fluoride bioavailability depends of at least four factors: fluoride formulation, time after fluoride application, fluoride concentration in supernatant saliva and fluoride concentration in salivary sediment 7 .…”
Section: Introductionmentioning
confidence: 99%